2008
DOI: 10.1111/j.1365-277x.2008.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of factors that influence the regular consumption of water by Irish primary school children

Abstract: The issues, opinions and perceived barriers raised by teachers as part of this qualitative research provide a basis for future health promotion around water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…The stronger influencer were family members (44.2%), which a variety of members were reported, siblings, grandparents as well as parents. This result highlights that teachers may not be ensuring adequately that children are hydrated within the school day, this may be due to the notion previously proposed 15 that teachers are not keen on their pupils drinking in lesson time due to distractions caused by taking time to consume, not then partaking in learning activities because of frequent visits to the toilets. This could indicate that teachers need further professional development to fully understand the benefits and also the limitations of effective hydration and the impact that this can have on their class of young children.…”
Section: Who Tells You To Drink?mentioning
confidence: 89%
“…The stronger influencer were family members (44.2%), which a variety of members were reported, siblings, grandparents as well as parents. This result highlights that teachers may not be ensuring adequately that children are hydrated within the school day, this may be due to the notion previously proposed 15 that teachers are not keen on their pupils drinking in lesson time due to distractions caused by taking time to consume, not then partaking in learning activities because of frequent visits to the toilets. This could indicate that teachers need further professional development to fully understand the benefits and also the limitations of effective hydration and the impact that this can have on their class of young children.…”
Section: Who Tells You To Drink?mentioning
confidence: 89%
“…Children should not have to ask for permission to drink water, and school staff should encourage students to stay hydrated. Restrictions in water access may lead to the absence of attention during classes and risks for pupils' well-being [31]. Although the school staff could be a positive force to empower hydration throughout the school day, only half of the students (47%) reported that they talked about the importance of drinking water.…”
Section: Wash: Education and Practicesmentioning
confidence: 99%
“…Children's bodies contain a higher percentage of water compared to adults and their larger surface area to volume ratio puts them at a greater risk of water loss through the skin when environmental temperatures rise 2 . As a result, there has been increasing interest into the effects of dehydration on children's cognitive function [3][4][5] , with one study in 10-12-year-olds reporting both a reduction in short-term memory scores and verbal tasks when dehydrated 6 .…”
Section: Introductionmentioning
confidence: 99%